Perancangan Galeri Seni Ukir Sebagai Citra Seni Arsitektur Identitas Lingkungan Kabupaten Jepara - Ariyanto Ariyanto; Ahmat Wakit; Teguh Tamrin (Jurnal Talenta Sipil, 2023)
Pursue the history of carving art in general and specifically in Jepara requires the expression of philosophy translation or transcendental approach of relationship between man and the Creator (magical inclination). The form of disclosure of the image of the most beautiful Creator becomes the intuition that is translated in the manifestations of the beauty of the works of nature. Art Carving as part of artwork in three dimensions that contain noble value from the expression of the glorification language of the beautiful image of the Creator. The salvation or preservation of the noble values of a work of carving, especially on the value of history and development in the modern era, requires a container that expresses functionally the Carving Art Gallery. Locations in Jepara as interactions of historical relationships and the development of art and educational image sustainability, as well as commercial carving furniture industry. The micro and macro demands of a Gallery complement the spectrum of manifestations in the art language of architecture and interpretation of environmental identity missions precedently. So that the design of Carving Art Gallery in Jepara embodies the functional demands of educative and commercial with more value than the art of environmental identity architecture.